The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1017/s1351324906004165
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between dialogue acts and learning in spoken tutoring dialogues

Abstract: We examine correlations between dialogue behaviors and learning in tutoring, using two corpora of spoken tutoring dialogues: a human-human corpus and a human-computer corpus. To formalize the notion of dialogue behavior, we manually annotate our data using a tagset of student and tutor dialogue acts relative to the tutoring domain. A unigram analysis of our annotated data shows that student learning correlates both with the tutor's dialogue acts and with the student's dialogue acts. A bigram analysis shows tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 9 publications
2
19
0
Order By: Relevance
“…In fact, it may be that different behaviors are actually optimally effective in computer and human tutors. This hypothesis is supported by our prior research, which has shown that although our students learn significantly from both our human tutor and ITSPOKE, their behaviors are very different (Forbes-Riley and Litman, 2008;Litman and Forbes-Riley, 2006b). However, we do not want to conclude that human tutor-based affect adaptations are less effective in general, because although our Complex adaptation was derived from statistical generalizations about human tutor responses to uncertainty, the effectiveness of these responses was not empirically tested before implementation.…”
Section: Evaluating the Adaptations: Student Learning Resultssupporting
confidence: 77%
“…In fact, it may be that different behaviors are actually optimally effective in computer and human tutors. This hypothesis is supported by our prior research, which has shown that although our students learn significantly from both our human tutor and ITSPOKE, their behaviors are very different (Forbes-Riley and Litman, 2008;Litman and Forbes-Riley, 2006b). However, we do not want to conclude that human tutor-based affect adaptations are less effective in general, because although our Complex adaptation was derived from statistical generalizations about human tutor responses to uncertainty, the effectiveness of these responses was not empirically tested before implementation.…”
Section: Evaluating the Adaptations: Student Learning Resultssupporting
confidence: 77%
“…Several recent studies of human tutorial dialogue have looked at particular aspects of restatements, for example, (Chi and Roy, 2010;Becker et al, 2011;Dzikovska et al, 2008;Litman and Forbes-Riley, 2006). One study examines face-toface naturalistic tutorial dialogue in which a tutor helps a student work through a physics problem (Chi and Roy, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Each dialogue contains 47 student turns and 43 tutor turns on average. This corpus was collected in tandem with a computer tutoring corpus using our ITSPOKE spoken dialogue tutoring system; the human tutor and ITSPOKE performed the same task [11]. Each dialogue consists of a question-answer discussion between tutor and student about one qualitative physics problem.…”
Section: Human Tutoring Spoken Dialoguesmentioning
confidence: 99%
“…Here we distinguish two labels 3 : the uncertain label is used for answers expressing uncertainty or confusion about the material being learned, and the non-uncertain label is used for all other answers. The same annotator also manually labeled each student answer for correctness, based on the human tutor's response to the answer [11]. Here we distinguish two labels 4 : the correct label is used for answers the tutor considered to be wholly or partly correct, and the incorrect label is used for answers the tutor considered to be wholly incorrect.…”
Section: Student Uncertainty and Correctness Annotationsmentioning
confidence: 99%